A COMPARATIVE STUDY OF BANK SOUNDNESS METHODS TO CORPORATE VALUE (Commercial Banks Listed on Indonesia Stock Exchange For 2017-2018 Period)) - Maharani Cegy Larasati; Tarmizi Achmad (Diponegoro Journal of Accounting, 2021)
In this study, the author wants to compare the bank soundness methods, namely the CAMELS and RGEC methods, by using corporate value as the performance indicator. This study uses 10 variables consisting of CAR, EAQ, OCOI, ROE, LDR, BETA which are the ratios of the CAMELS method, NPL, IRR, NIM, ROA, namely the ratios of the RGEC method, and Tobin’s Q ratio to calculate the corporate value.The population of this study is all commercial banks listed on the Indonesia Stock Exchange (IDX) during the 2017-2018 period. The sample was selected by using a purposive sampling method. This study has a total sample of 45 companies. The analysis technique in this study uses multiple regressionThe results of this study indicate that the OCOI and ROE ratios in the CAMELS method have a positive and significant effect on corporate value. In contrast, the NPL, IRR, and ROA ratios on the RGEC method also have a positive and significant effect on corporate value. From the results shown in this study, the author concludes that the RGEC method is more accurate and suitable for predicting the corporate value.